Giant prostatic hyperplasia in a 54-years old patient treated by prostate artery embolization: case report - Villard, Nicolas; Tsoumakidou, Georgia; Moldovan, Paul C.; Rosset, Rémy; Rouvière, Olivier; Fassi-Fehri, Hakim; Pagnoux, Gaële (Frontiers in Urology, 2024)
Giant prostatic hyperplasia (GPH) is defined as benign prostate hyperplasia (BPH) of more than 200 ml. It is a challenging condition because transurethral resection is classically indicated for prostate volume less than 80 ml and open adenectomy remains the gold standard therapy for GPH. Herein, we present the case of a 54-years old male with giant prostatic hyperplasia (total prostate volume of 265 ml) causing lower urinary tract symptoms (LUTS) and recurrent episodes of acute urinary retention. The patient refused the surgical adenomectomy and underwent bilateral prostate arteries embolization (PAE). Post embolization period was uneventful. Total prostate volume decreased progressively and LUTS disappeared. At more than 5 years follow-up the patient remains still asymptomatic, despite the discrete regrowth of the prostate detected on imaging. This case report suggests that PEA may be a good alternative to open surgery for patients with symptomatic GPH.